2012
DOI: 10.1021/cg3006162
|View full text |Cite
|
Sign up to set email alerts
|

Coordination-Induced Assembly of Coordination Polymer Submicrospheres: Promising Antibacterial and in Vitro Anticancer Activities

Abstract: Spheres-like coordination polymer architectures in submicro regimes have been synthesized from the hydrothermal reaction of transition metal ions and 3,5-bis(pyridin-3-ylmethylamino)benzoic acid (L1). The size of the final coordination polymer was dependent on the concentrations of reactants. Scanning electron microscopy studies monitored at numerous stages of growth reveal that coordination-induced morphology changes from uncoordinated flowerlike ligands to sphere-like coordination polymer particles. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(38 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…1g, in which the diffraction of these species can be readily indexed to small crystallinity, high crystallinity and amorphous state for CPP-1, CPP-2 and CPP-3, respectively. Our previous work demonstrated that controlling nucleation time and coordination equibrillium between different organic motifs and metal ions can effectively adjust the resulting size, morphology and crystallinity of CPPs, which is also the reason for explaining the experimental phenomenon happened [24,25].…”
Section: Resultsmentioning
confidence: 93%
“…1g, in which the diffraction of these species can be readily indexed to small crystallinity, high crystallinity and amorphous state for CPP-1, CPP-2 and CPP-3, respectively. Our previous work demonstrated that controlling nucleation time and coordination equibrillium between different organic motifs and metal ions can effectively adjust the resulting size, morphology and crystallinity of CPPs, which is also the reason for explaining the experimental phenomenon happened [24,25].…”
Section: Resultsmentioning
confidence: 93%
“…Wang et al have reported the synthesis and anticancer activity of photoluminescent sphere coordination particles obtained by reaction of different transition metal ions and 3,5-bis(pyridin-3-ylmethylamino)benzoic acid [53]. The size, growth, and morphology were found to depend on the concentrations of reactants, and variations of luminescent and antibacterial profiles are associated with coordination environments or the size of as-obtained coordination polymer samples.…”
Section: Active Metal Ionsmentioning
confidence: 99%
“…Incorporation of the active molecules in coordination polymer nanoparticles usually proceeds through two distinct strategies: 1) binding of the drug to the polymer framework as a CPP building block1014 and 2) mechanical entrapment of the therapeutic agent within the metal–organic matrix 1517. Accordingly, drug release can take place though different mechanisms, namely slow particle degradation through surface erosion, fast diffusion processes and/or a combination of both.…”
Section: Introductionmentioning
confidence: 99%